Identification and characterization of PKF118-310 as a KDM4A inhibitor. Issue 3 (4th March 2017) - Franci, Gianluigi; Sarno, Federica; Nebbioso, Angela; Altucci, Lucia
ABSTRACT: Epigenetic modifications are functionally involved in gene expression regulation. In particular, histone posttranslational modifications play a crucial role in functional chromatin organization. Several drugs able to inhibit or stimulate some families of proteins involved in epigenetic histone regulation have been found, a number of which are FDA-approved for the treatment of cutaneous T-cell lymphoma or are in phase I/II/III clinical trials for solid tumors. Although some protein families, such as histone deacetylases and their inhibitors, are well characterized, our understanding of histone lysine demethylases is still incomplete. We describe the in silico, in vitro, and cell-based characterization of the compound PKF118-310, an antagonist of transcription factor 4 (TCF4)/β-catenin signaling, as inhibitor of KDM4A. PKF118-310 potential inhibitor activity was discovered via virtual screening on the crystal structure of KDM4A. A peptide-based histone trimethylation assay developed in-house confirmed its potent KDM4A inhibitor activity. Its protein target was identified by cellular thermal shift assay experiments. PKF118-310 anticancer activity was observed in both liquid and solid tumor cells, and shown to have a dose- and time-dependent effect. We demonstrate the previously unreported inhibitory action of PKF118-310 on KDM4A. Our findings open up the possibility of developing the first KDM4A-specific inhibitors and derivatives.